Decision Support System For Evaluating The Performance Of Medical Personnel At Klinik Pratama Alwid Baroqah Using Vikor Method - Wahyu Al-Amar; Herlina Latipa Sari; Prahasti Prahasti (Jurnal Media Computer Science, 2026)
Klinik Pratama Alwid Baroqah is one of the health clinics located in Bengkulu City. Until now, the evaluation of medical staff performance has not been systematic, making it difficult for the management of Klinik Pratama Alwid Baroqah to make appropriate decisions regarding recommendations for contract extensions, termination of employment, or employment relationships. The Decision Support System for Evaluating the Performance of Medical Staff at Klinik Pratama Alwid Baroqah using Vikor Method can serve as an alternative in decision-making for evaluating the performance of medical staff at the clinic and can assist in providing performance evaluations of medical staff at the clinic, thereby making the evaluation process more structured and systematic. This Decision Support System was developed using Visual Basic Net programming language with SQL Server database. From the test data used, involving 10 medical staff during the evaluation period from July to December 2023, the results showed that with a Vikor index value range of 0.000–0.750, 8 medical staff had their employment contracts extended, while with a Vikor index value range of 0.917–1.000, 2 medical staff did not have their employment contracts extended. Based on the system testing conducted, it can be concluded that the decision support system application for evaluating the performance of medical staff at the Klinik Pratama Alwid Baroqah has been functioning well and successfully implemented Vikor method on the performance evaluation data of medical staff according to the evaluation period and year, and displayed recommendation results for decision-making regarding each medical staff member.